Konsep Insan Kamil Dalam Akhlak Nabi Muhammad SAW. Perspektif Quraish Shihab Dan Implikasinya Terhadap Pendidikan Islam - Rahmadani Akbar (El-Ihsan: Journal of Contemporary Islamic Education, 2025)
This article aims to examine the concept of insan kamil in the morals of the Prophet Muhammad SAW. based on the thoughts of Quraish Shihab, and its relevance to the paradigm of Islamic education. This study uses a qualitative approach through a literature study method with the main sources being the works of Quraish Shihab and Islamic education literature. The main finding of this article is that insan kamil in Quraish Shihab's perspective is a human being who actualizes divine values in real life, with the Prophet Muhammad SAW. as his ideal figure. He not only conveyed Islamic teachings normatively, but also represented them practically through his exemplary morals as a living educational model. In the context of Islamic education, the concept of insan kamil has implications for the goals, curriculum, methods, and evaluation of education. The goal is to form a person with noble character, the curriculum is integrative, the method is based on exemplary behavior, and the evaluation emphasizes character transformation. Therefore, Islamic education should adopt a holistic approach that not only forms intellectual intelligence, but also the spiritual depth and moral maturity of students as exemplified by the Prophet Muhammad SAW.